Peningkatan Minat Peduli Lingkungan Masyarakat Desa Buduan melalui Pelatihan Urban Farming dengan Media Tanam Hidrogel - Henny Rusmiyati; Ulil Azmi Nurlaili Afifah; Fitriani Eka Puji Lestari; Doni Sahat Tua Manalu; Harries Marithasari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Buduan Village, located in Suboh District, Situbondo Regency, East Java, is developing by continuously keeping up with the times so that rice fields are turned into buildings and structures. Buduan Village people's awareness of the environment still needs to grow, even though green open land is decreasing. Urban farming is introduced to the community to care for the environment and provide knowledge regarding several ways to grow crops on increasingly narrow land. Hydrogel is a planting medium in urban farming techniques that is easy to introduce to the public to increase interest in planting. The IPB Vocational School Homecoming Lecturer Team provided urban farming training using a planting system using hydrogel to the people of Buduan Suboh Village. This training activity aims to increase people's interest in planting. The training was carried out by providing urban farming material and continued with direct planting practice using hydrogel planting media. The Buduan Village Community attended this training from the Family Empowerment and Welfare (PKK) group and the Azzaidah recitation group; a total of 33 participants took part in the training. The results of this training provide knowledge about urban farming to the people of Buduan Suboh Village and the urban farming system. Planting using hydrogel media is implemented by the community in their respective home areas as an initial initiation into caring for the environment.